System for the Global Monitoring and Evaluation of Damage Processes Developing Within Concrete Structures Under Service Loads - Leszek Gołaski (The Baltic Journal of Road and Bridge Engineering, 2012)
In this paper, a global monitoring system based on the measurement of acoustic emission (AE) due to active deterioration processes is presented. This allows to examine the entire volume of an element and to locate (with an accuracy of the measuring zones) and identify the type and the dynamics of deterioration processes under service conditions. The resulting data are used to determine and locate the damage processes that are dangerous in construction and to assess the general condition of the structure as well as the degree of risk.